2018
DOI: 10.1007/s10661-018-6901-2
|View full text |Cite
|
Sign up to set email alerts
|

Water quality characteristics and corrosion potential in blending zones in X city drinking water distribution system

Abstract: Blended water, always existing in a drinking water distribution system (DWDS) with different sources, can cause some unintended results, including corrosion and/or release of corrosion by-products. Although some studies have specially focused on the blended water in DWDSs, the water quality characteristics, variations, and mechanisms for corrosion and metal release have not been fully understood. This study aims to examine the characteristics and evaluate the corrosion potential of blended water in X city DWDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In addition, the average sulfate and total dissolved solids concentration at Marston was 2 times higher than at Moffat (Table 1). Other studies have also found that blending of treated water from different sources in the drinking water distribution system can increase metals release which may explain the phenomenon observed in this study (Bradley & Horscroft, 2018;Zhang et al, 2018). Because all operational parameters were maintained during this period and this is a normal occurrence, these data were included in the analysis.…”
Section: Lead Release In Ph Adjustment and Orthophosphate Pipe Racksmentioning
confidence: 81%
“…In addition, the average sulfate and total dissolved solids concentration at Marston was 2 times higher than at Moffat (Table 1). Other studies have also found that blending of treated water from different sources in the drinking water distribution system can increase metals release which may explain the phenomenon observed in this study (Bradley & Horscroft, 2018;Zhang et al, 2018). Because all operational parameters were maintained during this period and this is a normal occurrence, these data were included in the analysis.…”
Section: Lead Release In Ph Adjustment and Orthophosphate Pipe Racksmentioning
confidence: 81%
“…High pH in water tends to cause numerous negative effects, including bitter taste, water pipes and water-using appliances being covered with a hard crust from deposits [27], and the effectiveness of disinfection processes using chlorine being affected [28]. Moreover, in terms of low-pH water, metals are likely to be corroded [29].…”
Section: Wastewater Characterizationmentioning
confidence: 99%
“…At home and abroad, the study of residual chlorine concentration in swimming pools has received extensive attention. Zhang, J et al [1] reviewed the methods for monitoring and evaluating residual chlorine in drinking water distribution systems, including traditional methods and emerging technologies, and discussed their advantages, disadvantages and applicability. Zhou, Y et al [2][3][4] evaluated the distribution of residual chlorine in a drinking water distribution system using a computational fluid dynamics model, and explored the effects of piping layouts and disinfectant dosing strategies on it.…”
Section: Introductionmentioning
confidence: 99%